GE_GERICHTE C/5493/2014 vom 4. April 2016 - GE Cour de justice (2016)
BANQUE ; EXÉCUTION DE L'OBLIGATION ; ORDRE DE PAIEMENT ; FALSIFICATION(ACTIVITÉ) ; CONDITIONS GÉNÉRALES DU CONTRAT ; FAUTE | CO.101; CO.398; CO.402;